Beside Du Côté de la côte (1958): Agnès Varda's early applied cinephilia. Issue 1 (1st May 2022) - Palmer, Tim
This article reappraises Agnès Varda's formative career as she made Du Côté de la côte in 1958. To do this, it explores Varda's situation within the post-war French film ecosystem before the French New Wave, how she engaged key practices of that overlooked era. By studying the ways Varda directly cites peer productions in Du Côté de la côte, we reveal her as heir to, and in dialogue with, a number of significant but neglected practitioners, notably women like Nicole Vedrès, Jacqueline Jacoupy and Yannick Bellon. Extrapolating from these creative protocols, we can properly gauge Varda's primary, and long-term, affinities for short films and essay films, two formats that film studies is often reluctant to recognize, let alone canonize. Nourishing Varda's work as a post-war short film essayist, we will also discover how applied cinephilia ‐ intertextual deployments of film history that catalyse actual filmmaking ‐ informed Varda's professional rise.